Awareness and attitude among general dentists and orthodontists toward obstructive sleep apnea in children - Arcidiacono, Luisa; Santagostini, Antonio; Tagliaferri, Sara; Ghezzi, Benedetta; Manfredi, Edoardo; Segù, Marzia (Frontiers in Neurology, 2024)
This study aimed to investigate Italian dentists' knowledge of and attitudes toward obstructive sleep apnoea (OSA) in children.An anonymous questionnaire was prepared using Google Forms and sent to dentists in Italy through private social platforms. The first part of the questionnaire contained basic demographic data questions, and the second part included items about paediatric OSA.A total of 125 responses were collected within one month. The interviews revealed gaps in undergraduate and post-graduate training on OSA, and consequently, low self-evaluation of knowledge and self-confidence in managing young patients with OSA. Dentists showed unfavorable attitudes and poor knowledge of the general findings, risk factors, and consequences of paediatric OSA, but demonstrated good knowledge of the beneficial effects of rapid maxillary expansion. Orthodontists showed a more favorable attitude and better recognition of the craniofacial features associated with OSA. In addition, a comparison was made between dentists who had graduated more than 5 years ago and new graduates, and differences were found in undergraduate education, which was better for new graduates, and a small number of questions were better answered by experienced dentists.This study showed a lack of knowledge about paediatric OSA and its management among Italian dentists, revealing the need to update the dentistry curriculum and organize educational interventions.